METRIK-MATH: Inovasi Media Pembelajaran Etnomatematika dalam Kearifan Lokal Candi Borobudur melalui Sistem Math City Maps Berbasis Hybrid Learning - Welda Warokhmah (Jurnal Ilmiah Matematika, 2026)
This research helps students understand mathematics learning, which they often consider difficult and intimidating. The study links mathematics learning to culture, referred to as ethnomathematics learning, by using Borobudur Temple as a local cultural object. The purpose of this research is to develop Math City Map learning media based on Hybrid Learning in ethnomathematics learning within the local wisdom of Borobudur Temple to help students learn mathematics easily and variably, analyze the influence of Borobudur Temple's local wisdom in ethnomathematics learning, and align technological advances in the mathematics learning process. The development method used is ADDIE; however, the researcher only utilizes three stages: Analyze, Design, and Development. The results of this study identified seven structures at Borobudur Temple that the researcher processed data from to be implemented into the Math City Map, namely garden benches, location maps, statue and site information boards, Jataka II reliefs, ojif, temple stairs, and boundary fences (bollards), which are applications of geometry topics, namely plane and solid shapes.